Large-eddy simulation on the similarity between wakes of wind turbines with different yaw angles. (25th August 2021) - Li, Zhaobin; Yang, Xiaolei
Abstract: Abstract : This work is dedicated to studying the similarity between wakes of wind turbines with different yaw angles and tip speed ratios under different turbulent inflows using large-eddy simulations with actuator surface models. Simulation results show that wake characteristics from cases with different yaw angles overlap with each other when normalized properly, which include the streamwise variations of the wake deflection, the centreline velocity deficit, the widths of the wakes, the standard deviations of instantaneous wake centre positions and the instantaneous wake widths. Different scalings are proposed for the streamwise velocity deficit and the transverse velocity. The similarities observed between cases with different yaw angles and the different scalings suggest that it is proper to decompose the wake of a yawed wind turbine into a streamwise wake and a lateral wake deflection, which is critical for developing analytical models. The mean of the instantaneous wake widths and the mean of the instantaneous centreline streamwise velocity are observed as being smaller than those of the time-averaged wake. These quantities are then related by using two analytical expressions proposed in this work. The observed similarities together with the proposed analytical expressions provide a better understanding of wakes of yawed wind turbines and can be employed to develop physics-based dynamic wake models.